2021
DOI: 10.3390/ijerph182111537
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Dynamics of Schistosoma haematobium among School-Aged Children: A Cohort Study on Prevalence, Reinfection and Incidence after Mass Drug Administration in the White Nile State of Sudan

Abstract: The reinfection rate of schistosomiasis after mass drug administration (MDA) has not been documented in Sudan. We aimed to explore the transmission dynamics of urogenital schistosomiasis after MDA, targeting school-aged children in the White Nile State of Sudan, assessing the prevalence, reinfection rate, and incidence. A single dose of praziquantel (40 mg/kg) was administered to 1951 students in five primary schools from January to February 2018 immediately after a baseline survey, and follow-up surveys were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…There were five longitudinal intervention studies [ 25 , 35 , 37 , 40 , 42 ], seven cluster randomized trials [ 23 , 24 , 27 29 , 32 , 35 ], one case control study [ 6 ], seven cross sectional studies [ 18 , 29 , 31 , 36 , 38 , 41 , 43 , 44 ], three prospective studies [ 15 , 19 , 33 , 39 ], two repeated cross sectional studies [ 24 , 34 ], longitudinal pre- and post- test design [ 16 ], one interventive prospective study [ 17 ] as shown in Fig 3 . Tanzania and Kenya had the most intervention studies, they each had five intervention studies included in this review whilst Zimbabwe and Ethiopia have four intervention studies, Cote’ d Ivoire has three intervention studies, Senegal and Nigeria had two intervention studies and Madagascar, Sudan, Niger, Angola and Togo each had one.…”
Section: Resultsmentioning
confidence: 99%
“…There were five longitudinal intervention studies [ 25 , 35 , 37 , 40 , 42 ], seven cluster randomized trials [ 23 , 24 , 27 29 , 32 , 35 ], one case control study [ 6 ], seven cross sectional studies [ 18 , 29 , 31 , 36 , 38 , 41 , 43 , 44 ], three prospective studies [ 15 , 19 , 33 , 39 ], two repeated cross sectional studies [ 24 , 34 ], longitudinal pre- and post- test design [ 16 ], one interventive prospective study [ 17 ] as shown in Fig 3 . Tanzania and Kenya had the most intervention studies, they each had five intervention studies included in this review whilst Zimbabwe and Ethiopia have four intervention studies, Cote’ d Ivoire has three intervention studies, Senegal and Nigeria had two intervention studies and Madagascar, Sudan, Niger, Angola and Togo each had one.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying hotspots is critical for the interruption of transmission. After 10 years of continuous MDA interventions in the White Nile state, the prevalence of schistosomiasis has remained high in some villages and schools due to persistent reinfection [33][34][35]. As part of the SENSE project, snail control and sanitation improvements through community-led total sanitation (CLTS) complement the existing MDA program.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated praziquantel dosing may thus be required to achieve a full cure. Mass drug administration, used in endemic settings, does not prevent reinfection and in exposed populations, the disease prevalence returns to its original level within 6–8 months [ 11 ]. There are also concerns about the possible emergence of drug resistance following repeated intervention with a single drug [ 12 ].…”
Section: Introductionmentioning
confidence: 99%